에탄올 음용으로 유도된 발기부전 동물모델에 대한 구기자 추출물의 개선효과 - 정세희(Se Hee Jung); 김정훈(Jung Hoon Kim); 오홍근(Hong Geun Oh); 신은혜(Eun Hye Shin); 이봉근(Bong Gun Lee); 박상훈(Sang Hoon Park); 문대인(Dae In Moon); 박영미(Young Mi Park); 한주희(Ju Hee Han); 한종현(Jong Hyun Han); 박광현(Kwang Hyun Park); 박종상(Jong Sang Park); et al. (동의생리병리학회지, 2013)
Erectile dysfunction (ED) is a highly prevalent disorder that affects millions of men worldwide. ED is now considered an early manifestation of atherosclerosis, and consequently, a precursor of systemic vascular disease. Lycii fructus extracts (LFE) were administered for 4 weeks to assess the improving effects on ED. Animals were divided into one normal group and four LFE-treated groups (0, 0.3, 0.6, and 1.2 g/kg). We induced ED in the study animals by oral administration of 20% ethanol instead of water everyday for 4 weeks. This study was designed to investigate the effects of LFE on the mRNA levels of inducible nitric oxide synthase (iNOS) and endothelial NOS (eNOS) expression; NO levels of nitric oxide (NO) and cyclic guanosine monophosphate (cGMP); blood profile; and erectile response of the corpus cavernosum of the rat penis. The libido of the LFE-administered male rats was higher than that of the ethanol control group. The erectile response of the corpus cavernosum was restored after LFE administration, to a level similar to the normal group. In addition, the iNOS in the corpus cavernosum of the male rats administered LFE decreased. In contrast, compared to the control group, LFE-administered male rats showed increased eNOS, NO and cGMP levels in the corpus cavernosum. These results indicate that LFE effectively restored ethanol-induced ED in male rats.